Expressão do antígeno A1: frequência em recém-nascidos - Mikalauscas, Márcia Maria Vasconcellos (2011)
Within the ABO system there are several blood subgroups: subgroup A, subgroup B and subgroup H, and the most frequently encountered in practice are the subgroups A1, A2, A1B and A2B. The cells of, approximately, 80% of adults in group A are A1. The remaining 20% are A2 or weaker subgroups. However, in newborns is very little literature about the frequency of the subgroups of A. At birth most of the blood group A infants seems to present itself as belonging to subgroup A2, since all the ABO antigens are not fully developed in this period. Since iron deficiency, widespread in this age group, often discussed by the scientific community is related to the disproportion between the expansion of erythroid mass and iron obtained from the diet. Around four months of age, iron stores are reduced by half, and the exogenous iron is required to maintain hemoglobin concentration during this phase of rapid growth, between four and 12 months. Our objectives were to determine the frequency of newborns belonging to subgroups A1 and A2, to identify the frequency of antigen expression A1, between six and 12 months of age, infants initially typed as belonging to subgroup A2 and check the hemoglobin levels for the detection of anemia in these children. The results showed that the frequency of newborn belonging to the A1 blood subgroup was 67% (319) and the A2 subgroup was 33% (152), from a total of 471 newborns belonging to blood group A. We found a great predominance of the A1 subgroup, contradicting the literature that reports the prevalence of subgroup A2 in newborn infants. Regarding the identification of the frequency of A1antigen expression, between six and 12 months of age (n = 40), the percentage of children who express the A1 antigen, after being with six months to one year of age was 67.5% (27), the rest remained as A2 (13). The verification of hemoglobin levels in these children (n = 71), by the method of cianometa-hemoglobin, resulting in 34% of anemic children, pointing to the presence of anemia in this age group. The rates found ranged from 6.56 g/dl to 10.8 g/dl. Thus, in relation to A1 antigen expression between six and 12 months of age further studies are needed, and for the prevalence of anemia is necessary to emphasize in public health programs, intervention measures and more effective control of this nutritional disorder.